Mergers, acquisitions, and other restructuring activities : an integrated approach to process, tools, cases, and solutions - DePamphilis, Donald M. (Amsterdam ; Boston : Academic Press, 2003)
Filled with updated cases and grounded models which reflect the theoretical underpinnings of the field. Expanded usage of key idea section headings enable the student to understand more easily the key point in each section of each chapter.
Includes bibliographical references and index.
oif 03/01/15
Loans
Keywords: Consolidation and merger of corporations; Corporate reorganizations; Management buyouts; Consolidation and merger of corporations; Organizational change; Corporate divestiture